Pengaruh Penerapan Core Tax Administration System, Persepsi Wajib Pajak, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di KPP Pratama Bekasi Utara - Annisa Fitriani Dewi; Imam Susanto (Jurnal Ilmu Administrasi Publik, 2025)
Variations in individual taxpayer (WPOP) compliance at KPP Pratama Bekasi Utara reflect the inherent complexity of tax reporting and payment behaviors. Despite a consistent annual increase in the number of registered individual taxpayers, the figures for those obligated to submit Annual Tax Returns (SPT) exhibit irregular and fluctuating trends. The implementation of the Core Tax Administration System (CTAS), taxpayers’ perceptions, and the enforcement of tax penalties for late submission are presumed to be key factors influencing compliance levels. This study seeked to examine the extent to which these three variables impact individual taxpayer compliance, both independently and collectively. Adopting a quantitative research design, the study utilized purposive sampling and applied multiple linear regression analysis through SPSS version 27. Findings indicated that while CTAS contributes 44.4% to compliance, its influence is not statistically significant when considered in isolation. Conversely, taxpayer perceptions and tax sanctions accounted for 61.5% and 51.2% respectively, with both demonstrating a significant and positive effect. When assessed simultaneously, the three variables collectively accounted for 65.1% of the variance in taxpayer compliance, underscoring the necessity of an integrated and behaviorally informed approach to enhancing fiscal compliance. Keywords Core Tax Administration System, Taxpayer Perceptions, Tax Sanctions, Taxpayer Compliance, Quantitative Method.